2012
DOI: 10.1371/journal.pone.0049378
|View full text |Cite
|
Sign up to set email alerts
|

Murine Myeloid Dendritic Cells That Phagocytose Apoptotic T Cells Inhibit the Immune Response via NO

Abstract: The contraction phase of antigen-specific immune responses involves the apoptotic loss of numerous activated lymphocytes. While apoptotic cells are known to induce immune suppression, the mechanisms involved therein are still ambiguous. Some reports have speculated that macrophages can induce regulatory T cells (Tregs) after engulfing apoptotic cells. In this study, we showed that dendritic cells (DCs) that phagocytose apoptotic T cells acquire inhibitory function (named DCapos) toward CD4+ and CD8+ T cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
(84 reference statements)
0
17
0
Order By: Relevance
“…In turn, DCs co-cultured with apoptotic cells up-regulate iNOS generation and STAT3 phosphorylation and can induce regulatory T cells after engulfing apoptotic cells. Importantly, DCs that phagocytose apoptotic T cells acquire inhibitory function toward CD4 + and CD8 + T cells [93]. These regDCs could not induce the generation of Tregs, but they were found to directly inhibit conventional DCs that initiate CD4 + and CD8 + T cell proliferation both in vitro and in vivo.…”
Section: Additional Tolerogenic Pathways In Regdcsmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, DCs co-cultured with apoptotic cells up-regulate iNOS generation and STAT3 phosphorylation and can induce regulatory T cells after engulfing apoptotic cells. Importantly, DCs that phagocytose apoptotic T cells acquire inhibitory function toward CD4 + and CD8 + T cells [93]. These regDCs could not induce the generation of Tregs, but they were found to directly inhibit conventional DCs that initiate CD4 + and CD8 + T cell proliferation both in vitro and in vivo.…”
Section: Additional Tolerogenic Pathways In Regdcsmentioning
confidence: 99%
“…These regDCs could not induce the generation of Tregs, but they were found to directly inhibit conventional DCs that initiate CD4 + and CD8 + T cell proliferation both in vitro and in vivo. Soluble factors including NO play a role in the DC-induced suppression of CD4 + and CD8 + T cell proliferation [93].…”
Section: Additional Tolerogenic Pathways In Regdcsmentioning
confidence: 99%
“…The phenotypes and functions of these cells are highly plastic and modifiable by factors in the ambient environment [13,14]. Our and other's studies have shown that some special microenvironments can drive mature and immature DCs to differentiate into regulatory DCs, thereby suppressing their ability to induce CD4 + T responses [15][16][17][18]. Activated CD8 + T cells express many adhesion molecules on the cell membrane, and secret different cytokine profiles from its quiescent state.…”
Section: Introductionmentioning
confidence: 94%
“…Western blotting was done as previous reported [17]. In brief, protein was extracted from DCs by lysis buffer and boiled for 10 min.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Besides IDO, regulatory DCs (in addition to macrophages) also produce arginase, which utilizes L-arginine (Norian, et al, 2009; Scarlett, et al, 2012), at least in mouse tumor models. Finally, as their immature myeloid precursors, regulatory DCs can also produce iNOS, responsible for inhibiting immune responses through nitric oxide production (Zhong, et al, 2012). …”
Section: Mechanisms Of Immunosuppression Elicited By Regulatory Dcsmentioning
confidence: 99%